Examination of the Behavior of Gravity Quay Wall against Liquefaction under the Effect of Wall Width and Soil Improvement. (10th July 2014) - Firoozi, Ali Akbar; Taha, Mohd Raihan; Mir Moammad Hosseini, S. M.; Firoozi, Ali Asghar
Abstract : Deformation of quay walls is one of the main sources of damage to port facility while liquefaction of backfill and base soil of the wall are the main reasons for failures of quay walls. During earthquakes, the most susceptible materials for liquefaction in seashore regions are loose saturated sand. In this study, effects of enhancing the wall width and the soil improvement on the behavior of gravity quay walls are examined in order to obtain the optimum improved region. The FLAC 2D software was used for analyzing and modeling progressed models of soil and loading under difference conditions. Also, the behavior of liquefiable soil is simulated by the use of "Finn" constitutive model in the analysis models. The "Finn" constitutive model is especially created to determine liquefaction phenomena and excess pore pressure generation.